2020
DOI: 10.2147/ppa.s235107
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association Among Medication Beliefs, Perception of Illness and Medication Adherence in Ischemic Stroke Patients: A Cross-Sectional Study in China</p>

Abstract: To examine the association and the mediating effect among medication beliefs, perception of illness, and medication adherence in ischemic stroke patients. Patients and Methods: This is a cross-sectional study, 306 ischemic stroke patients recruited from The Second Affiliated Hospital of Harbin Medical University, China between June 2018 and October 2018. The Beliefs about Medications Questionnaire (BMQ) was used to assess a patient's beliefs about medication. The Brief Illness Perceptions Questionnaire (BIPQ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 43 publications
1
35
0
1
Order By: Relevance
“…The focus of the present study on rheumatic disease management is congruent with the problem faced by rheumatology communities these days. 45,46 Medication non-adherence could lead to increased morbidity, mortality, and healthcare costs. 47,48 However, patients who have misperceptions might be more likely to adhere to their medication if they experienced disease acceptance, therapeutic benefits, or fear of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of the present study on rheumatic disease management is congruent with the problem faced by rheumatology communities these days. 45,46 Medication non-adherence could lead to increased morbidity, mortality, and healthcare costs. 47,48 However, patients who have misperceptions might be more likely to adhere to their medication if they experienced disease acceptance, therapeutic benefits, or fear of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As such patients who perceived that their disease activity had worsened since the COVID‐19 outbreak were more likely to be not adherent to their medications compared to those with a positive perception. Studies suggested that patients who have poor health perception might adhere less because of misbelief and maladaptive behavior 45,46 . Medication non‐adherence could lead to increased morbidity, mortality, and healthcare costs 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, there is evidence in literature that patient–healthcare provider mistrust was considered as a major problem that has become a common part of the Chinese patient experience [ 41 ]. Patient trust may influence patients’ willingness to continue taking their medications and to stop perceiving their medications as overused [ 42 ]. One of the practical strategies to support this is to encourage healthcare providers to provide care that is concordant with the patient’s values, needs, and preferences, and that allows patients to provide their own input and participate actively in decisions regarding their medications and health [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an indicator of health in general, health perception is a significant predictor of health outcomes, such as quality of life and health behaviors, affecting disease prognosis and health status [ 23 ]. Nonsmoking status, regular physical activity, healthy diet, adherence to medication and medical recommendations, and psychological well-being are associated with higher perceived health status [ 24 , 25 , 26 , 27 ]. However, the results of studies exploring the interaction between a healthy lifestyle and subjective health perception are not consistent [ 28 ].…”
Section: Introductionmentioning
confidence: 99%